Efficiency in administration: Measures required to enhance efficiency in administration - Sharma, R.D. (2007)
Efficiency in administration broadly involves a value, a goal or a criterion to assess the effectiveness of system. The personnel are adjudged by their motivation and capacity to attain maximum value with limited means. This article takes an overview of various definitions of administrative efficiency advanced by authorities on public administration. It evaluates Indian civil services and public organisations on the emerging criterion of efficiency. An assessment has been made here of the successive attempts at administrative reforms and by way of conclusion a number of suggestions have been made to instill greater efficiency in administration at various levels. - Reproduced.
Keywords: Public administration